2011
DOI: 10.1242/jcs.077388
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin-generated tension controls the molecular kinetics of focal adhesions

Abstract: SummaryFocal adhesions (FAs) have key roles in the interaction of cells with the extracellular matrix (ECM) and in adhesion-mediated signaling. These dynamic, multi-protein structures sense the ECM both chemically and physically, and respond to external and internal forces by changing their size and signaling activity. However, this mechanosensitivity is still poorly understood at the molecular level.Here, we present direct evidence that actomyosin contractility regulates the molecular kinetics of FAs. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
182
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(206 citation statements)
references
References 51 publications
23
182
0
1
Order By: Relevance
“…4F). On a 2D surface, t 1/2 values for vinculin were longer than those for paxillin, which accords with other recent investigations (Wolfenson et al, 2011). Comparisons of data collected on 1D and 2D substrates revealed a twofold increase in vinculin t 1/2 rates, which were analogous to the paxillin t 1/2 rates analyzed by FRAP (Fig.…”
Section: Adhesion Longevity Depends On the Cellular Microenvironmentsupporting
confidence: 91%
“…4F). On a 2D surface, t 1/2 values for vinculin were longer than those for paxillin, which accords with other recent investigations (Wolfenson et al, 2011). Comparisons of data collected on 1D and 2D substrates revealed a twofold increase in vinculin t 1/2 rates, which were analogous to the paxillin t 1/2 rates analyzed by FRAP (Fig.…”
Section: Adhesion Longevity Depends On the Cellular Microenvironmentsupporting
confidence: 91%
“…Taken together, these data suggest that in wild-type cells β-PIX promotes disassembly of FA via an ability to induce actomyosin relaxation, whereas its loss results in enhanced myosin-mediated actin cytoskeleton contraction leading to an inhibition in FA disassembly. This conclusion is supported by work from others who have shown that the actin cytoskeleton regulates FA disassembly through the regulation of actomyosin tension (Wolfenson et al, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, kinetic analyses have recently demonstrated the involvement of myosin II in the timely maturation of FX and FA. 7,10,11 The biological mechanisms deciphering how myosin II functions in FA maturation remain to be fully unraveled, but could be through either the generation of tension, which directly affects the conformation of proteins in the adhesion complex 12 or its cross-linking activity. 11,13 Consequently, factors that can regulate both myosin II's cross-linking activities and contraction are good candidates to govern FA formation.…”
Section: S100a4 Downregulates Filopodia Formation Through Increased Dmentioning
confidence: 99%
“…Such possibility is supported by recent findings demonstrating the importance of myosin II in the timely maturation of focal complexes (FX) and FA. 7,10,11 Such lack of maturation would, therefore, lead to filopodial retraction and a low number of FAs resulting in the observed effects on morphology and migration. The reasons for S100A4 to induce such effects through myosin IIA remain to be explicitly demonstrated.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%